2019
DOI: 10.1002/chem.201806132
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Induced Reactions in 3‐Bromopyruvic Acid

Abstract: 3-Bromopyruvic acid (3BP) is ap otential anticancer drug, the action of which on cellular metabolism is not yet entirely clear.T he presenceo fabromine atom suggests that it is also reactive towards low-energy electrons, which are produced in large quantities during tumour radiation therapy.D etailed knowledge of the interaction of 3BP with secondary electrons is aprerequisite to gain acomplete picture of the effects of 3BP in different forms of cancer therapy.H erein, dissociative electron attachment (DEA) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Previous studies showed that DEA can be an effective process in breaking bonds and hence generates radicals at electron energies considerably below typical bond dissociation energies [10,11,12,13,14]. Such behavior was also observed in DEA studies with radiosensitizers like modified nucleobases [5,6,17,18,19,20]. By modification of the native nucleobase by highly electron affinic side groups, an increase of the DEA cross section can be achieved.…”
Section: Introductionmentioning
confidence: 75%
“…Previous studies showed that DEA can be an effective process in breaking bonds and hence generates radicals at electron energies considerably below typical bond dissociation energies [10,11,12,13,14]. Such behavior was also observed in DEA studies with radiosensitizers like modified nucleobases [5,6,17,18,19,20]. By modification of the native nucleobase by highly electron affinic side groups, an increase of the DEA cross section can be achieved.…”
Section: Introductionmentioning
confidence: 75%
“…3-BP treatment probably leads to generation of ROS through its cellular metabolism, by damaging mitochondria and as a result of GSH depletion [20,26,27]. Recent studies also show that 3-BP may directly disrupt the OXPHOS electron transport chain in mitochondria and thereby induce ROS [65]. It is also known that at least some chemical oxidants such as H 2 O 2 or bleomycin are able to induce both SSBs and DSBs [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…3-BP exhibits broad activities, from anticancer [3,69], antifungal [65,70] to antibacterial [71] and anti-algal [72]. 3-BP, in the cell, acts pleiotropically by disrupting various processes (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…The reaction enthalpy of electron-induced dehydrogenation of HCOOH can be described as a balance between the electron affinity of the HCOO (i.e., 3.17 eV [ 31 ]) and the HCOO-H bond dissociation energy (i.e., 4.47 eV [ 31 ]). In contrast, for the acetic acid, the pyruvic acid, the benzoic acid and the bromopyruvic acid this threshold is considerably below 1 eV [ 32 , 33 , 34 , 35 ]. In the present case, for both molecules, we observe the threshold for the molecular dehydrogenation near 0 eV ( Figure 2 a, m/z 131 and Figure 3 a, m/z 191).…”
Section: Resultsmentioning
confidence: 99%